Confirmatory factor analysis of the valencia scale of attitudes and beliefs toward hypnosis (revised client version), with a spanish sample. - Capafons, Antonio; Suárez-Rodríguez, Jesús M.; Selma, Mª Luisa (Anales de Psicología / Annals of Psychology, 2014)
Several approaches to hypnosis have highlighted the importance of attitudes and beliefs on it to promote hypnotic responses, their power to predict the efficacy of interventions that include hypnosis, as well as to generate or prevent iatrogenic reactions in patients. The goal of this study is to investigate the new variation of the Valencia Scale of Attitudes and Beliefs toward Hypnosis Client version, written in Castilian. The scale was analyzed using confirmatory methodology to obtain its factor structure and psychometric properties, in order to confirm the results of previous exploratory and confirmatory research, with samples from different countries.  A sample of 1.678 Spanish university students was used this time. Data show an eight factors structure (Fear, Memory, Help, Control, Collaboration, Interest, Magic and Marginal), and an appropriate internal consistency and test-retest reliability. Results are similar to those found in previous exploratory and confirmatory factorial analysis conducted in different countries.